Shielding implications for secondary neutrons and photons produced within the patient during IMPT. Issue 7 (31st May 2013) - DeMarco, J.; Kupelian, P.; Santhanam, A.; Low, D.
Abstract : Purpose: : Intensity modulated proton therapy (IMPT) uses a combination of computer controlled spot scanning and spot‐weight optimized planning to irradiate the tumor volume uniformly. In contrast to passive scattering systems, secondary neutrons and photons produced from inelastic proton interactions within the patient represent the major source of emitted radiation during IMPT delivery. Various published studies evaluated the shielding considerations for passive scattering systems but did not directly address secondary neutron production from IMPT and the ambient dose equivalent on surrounding occupational and nonoccupational work areas. Thus, the purpose of this study was to utilize Monte Carlo simulations to evaluate the energy and angular distributions of secondary neutrons and photons following inelastic proton interactions within a tissue‐equivalent phantom for incident proton spot energies between 70 and 250 MeV. Methods: : Monte Carlo simulation methods were used to calculate the ambient dose equivalent of secondary neutrons and photons produced from inelastic proton interactions in a tissue‐equivalent phantom. The angular distribution of emitted neutrons and photons were scored as a function of incident proton energy throughout a spherical annulus at 1, 2, 3, 4, and 5 m from the phantom center. Appropriate dose equivalent conversion factors were applied to estimate the total ambient dose equivalent from secondary neutrons and photons. Results: : A reference distance of 1 m from the center of the patient was used to evaluate the mean energy distribution of secondary neutrons and photons and the resulting ambient dose equivalent. For an incident proton spot energy of 250 MeV, the total ambient dose equivalent (3.6 × 10 −3 mSv per proton Gy) was greatest along the direction of the incident proton spot (0°–10°) with a mean secondary neutron energy of 71.3 MeV. The dose equivalent decreased by a factor of 5 in the backward direction (170°–180°) with a mean energy of 4.4 MeV. An 8 × 8 × 8 cm 3 volumetric spot distribution (5 mm FWHM spot size, 4 mm spot spacing) optimized to produce a uniform dose distribution results in an ambient dose equivalent of 4.5 × 10 −2 mSv per proton Gy in the forward direction. Conclusions: : This work evaluated the secondary neutron and photon emission due to monoenergetic proton spots between 70 and 250 MeV, incident on a tissue equivalent phantom. Example calculations were performed to estimate concrete shield thickness based upon appropriate workload and shielding design assumptions. Although lower than traditional passive scattered proton therapy systems, the ambient dose equivalent from secondary neutrons produced by the patient during IMPT can be significant relative to occupational and nonoccupational workers in the vicinity of the treatment vault. This work demonstrates that Monte Carlo simulations are useful as an initial planning tool for studying the impact of the treatment room and maze design on surrounding occupational and nonoccupational work areas.